An experimental study on the effect of lobe swirl device and its transition parts on thermal performance using Graphene-CuO/water nanohybrid - Farag A. Diabis; Abd Rahim Abu Talib; Norkhairunnisa Mazlan; Eris Elianddy Supeni (Case Studies in Thermal Engineering)
Enhancing heat transfer efficiency is a key focus in thermal applications. Smooth channels often suffer from poor fluid mixing, limiting their performance. Swirl flow techniques have been introduced to improve heat exchanger efficiency by altering flow direction and inducing turbulence. However, integrating nanofluids with swirl techniques presents challenges such as increased pressure loss and nanoparticle sedimentation. The four-lobed swirl generator is a promising solution, delivering high swirl intensity with manageable pressure loss. This study explores the impact of GO-CuO/water hybrid nanofluid and Reynolds numbers on the thermal performance of a four-lobed swirl generator. The system parameters include a twisted angle (θ = 360°), β-transition type, transition multiplier (n = 0.5 mm), and a variable helix (t = 1). The hybrid nanofluid, synthesized with a 20 % GO to 80 % CuO ratio, has volume concentrations of 0.15%–0.75 % wt., with Reynolds numbers from 15,000 to 35,000. Results indicate a significant heat transfer enhancement (1.26–1.72 times) with a moderate friction factor increase (1.27–1.53). The highest thermal performance (1.511) occurs at 0.75 % nanofluid concentration and Re = 25,000. This study confirms the four-lobed swirl generator's effectiveness in improving heat exchanger efficiency while maintaining an acceptable pressure drop.